2016
DOI: 10.12659/msm.895967
|View full text |Cite
|
Sign up to set email alerts
|

A Hearing Screening Program for Children in Primary Schools in Tajikistan: A Telemedicine Model

Abstract: BackgroundAccording to the guidelines of the European Scientific Consensus on Hearing (European Federation of Audiology Societies ‘EFAS’ Congress, June 2011, Warsaw, Poland), the detection and treatment of communication disorders in early school-age children is of the highest importance. This objective was adopted by the Polish president of the EFAS Council from the second half of 2011; as a result, pilot programs on children’s hearing screening were initiated in various European countries. This paper reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
19

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(114 citation statements)
references
References 31 publications
5
90
0
19
Order By: Relevance
“…Studies that used a similar age group found different prevalences: in Canada, the prevalence was 4.7%, established through an association between a 0.5-8 kHz threshold of hearing and otoacoustic emissions; 27 in Bangladesh, the prevalence was 13% for incapacitating hearing loss, through 0.5-4 kHz threshold of hearing and otoacoustic emissions. 12 In studies that utilized the same frequencies in auditory evaluation, [28][29][30][31] the pass-criterion at 20dB was not adopted. However, the prevalence found in the present study was still high, compared with previous studies and with prevalence values of 4.92% in China, 30 2.4% in Zimbabwe, 29 10.3% of fails in Poland, 31 but lower than the 33% value found in Oman.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that used a similar age group found different prevalences: in Canada, the prevalence was 4.7%, established through an association between a 0.5-8 kHz threshold of hearing and otoacoustic emissions; 27 in Bangladesh, the prevalence was 13% for incapacitating hearing loss, through 0.5-4 kHz threshold of hearing and otoacoustic emissions. 12 In studies that utilized the same frequencies in auditory evaluation, [28][29][30][31] the pass-criterion at 20dB was not adopted. However, the prevalence found in the present study was still high, compared with previous studies and with prevalence values of 4.92% in China, 30 2.4% in Zimbabwe, 29 10.3% of fails in Poland, 31 but lower than the 33% value found in Oman.…”
Section: Discussionmentioning
confidence: 99%
“…One example of effective international program for telemapping and telerehabilitation are the programs of the World Hearing Center Institute of Physiology and Pathology of Hearing in former Soviet Union countries and Africa (39). These projects are often connected with hearing screening projects in school-age children (40). Studies of these telehealth systems applied to cochlear implantation demonstrated high savings to the patient and patient satisfaction, particularly for follow-up mapping sessions (39,40).…”
Section: Improving Cost Effectiveness By Reducing Costsmentioning
confidence: 99%
“…These projects are often connected with hearing screening projects in school-age children (40). Studies of these telehealth systems applied to cochlear implantation demonstrated high savings to the patient and patient satisfaction, particularly for follow-up mapping sessions (39,40).…”
Section: Improving Cost Effectiveness By Reducing Costsmentioning
confidence: 99%
“…Especially in developing countries, different audiometric examinations were tested in order to improve the telemedical identification of hearing impairment [43,[93][94][95][96][97][98][99][100][101][102]. With use of a computer-assisted audiometer in comparison to double-blind, conventional audiometry, a comparative investigation revealed an accuracy of 1.3 dB for measurement values of air conduction and 1.2 dB for bone conduction [103,104].…”
Section: Tele-audiometric Examinationsmentioning
confidence: 99%